Thyroid Storm Presenting with Isolated Acute Bulbar Myopathy: A Case Report and Literature Review - AlNeyadi, Asma; AlKhanbashi, Manal; AlKaabi, Fatima; Ismail, Mohamed (Journal of Diabetes and Endocrine Practice, 2022)
While proximal skeletal muscle myopathy is a frequently reported complication of thyrotoxicosis, acute bulbar thyrotoxic myopathy is rare especially in absence of other forms of myopathy. In this report, we present a case of 31 years old male presenting with thyrotoxicosis and aspiration pneumonia following weeks of experiencing dysphagia and hoarseness of voice. Labs confirmed Graves' disease and other causes of bulbar myopathy like Myasthenia gravis was ruled out. He was started on thyroid treatment and showed remarkable improvement of dysphagia over 15 days. Based on this, we conclude that isolated bulbar myopathy in hyperthyroidism should be considered in patients presenting with dysphagia and dysphonia in absence of other possible neurological causes.
Keywords: bulbar myopathy; Graves' disease; thyrotoxic myopathy